Rapid evaluation of FDG imaging alternatives using head-to-head comparisons of full ring and gamma camera based PET scanners – - Haslinghuis-Bajan, L. M.; Hooft, L.; van Lingen, A.; van Tulder, M.; Devillé, W.; Mijnhout, G. S.; Teule, G. J. J.; Hoekstra, O. S. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: While FDG full ring PET (FRPET) has been gradually accepted in oncology, the role of the cheaper gamma camera based alternatives (GCPET) is less clear. Since technology is evolving rapidly, “tracker trials” would be most helpful to provide a first approximation of the relative merits of these alternatives. As difference in scanner sensitivity is the key variable, head-to-head comparison with FRPET is an attractive study design. This systematic review summarises such studies. Methods: Nine studies were identified until July 1, 2000. Two observers assessed the methodological quality (Cochrane criteria), and extracted data. Results: The studies comprised a variety of tumours and indications. The reported GC- and FRPET agreement for detection of malignant lesions ranged from 55 to 100%, but with methodological limitations (blinding, standardisation, limited patient spectrum). Mean lesion diameter was 2.9 cm (SD 1.8), with only about 20% <1.5 cm. The 3 studies with the highest quality reported concordances of 74-79%, for the studied lesion spectrum. Contrast at GCPET was lower than that of FRPET, contrast and detection agreement were positively related. Logistic regression analysis suggested that pre-test indicators might be used to predict FRPET-GCPET concordance. Conclusion: In spite of methodological limitations, “first generation” GCPET devices detected sufficient FRPET positive lesions to allow prospective evaluation in clinical situations where the impact of FRPET is not confined to detection of small lesions (<1.5 cm). The efficiency of head-to-head comparative studies would benefit from application in a clinically relevant patient spectrum, with proper blinding and standardisation of acquisition procedures.
Keywords: PET; coincidence detection; 18F-FDG; neoplasma